HUBUNGAN ANTARA KUALITAS DESTINASI PARIWISATA MAKASSAR DENGAN TINGKAT PENGALAMAN BERWISATA DAN KEPUTUSAN LAMA TINGGAL WISATAWAN - , PRATIWI CAHYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of the research is to find the correlation between the quality of Makassar tourism destination with the level of touristâs experience and the decision of touristâs length of stay. Research method that is used is descriptive and quantitative. This research is located in Makassar City, pointed to the perceptions of domestic tourists and foreign tourists who have visited and used the tourism components in the related destination. The research findings are: (1) The quality of Makassar tourism destination based on the perception of domestic and foreign tourist who have visited and used the tourism components in that destination (2) The level of tourist experience in Makassar tourism destination (3) The correlation between the quality of Makassar tourism destination and the level of touristâs experience (4) The component of Makassar tourism destination that has the most significant correlation with the level of touristâs experience (5) The decision of touristâs length of stay in Makassar tourism destination (6) The correlation between the quality of Makassar tourism destination and the decision of touristâs length of stay (7) The component of Makassar tourism destination that has the most significant correlation with the decision of touristâs length of stay. Result of the research can be concluded as: (1) Difference in perceptions between domestic tourists and foreign tourists are seen on the quality rating of informations and local souvenir shopping centers in Makassar tourism destination (2) Both domestic tourists and foreign tourists have the same perceptions about their level of touristâs experience those are positive perceptions (memorable and very memorable) (3) Correlation between the quality of Makassar tourism destination with the level of touristâs experience is positive correlation (directly propotional) (4) Both domestic tourists and foreign tourists rate the quality of information as the tourism component that has the most significant correlation with their the level of touristâs experience (5) Domestic tourists tend to extend their length of stay and foreign tourists tend to not to change even shorten their length of stay in Makassar tourism destination (6) Correlation between the quality of Makassar tourism destination with the decision of touristâs length of stay is positive perception (directly propotional) (7) Component of destination that has the most significant correlation with the decision of touristâs length of stay in Makassar tourism destination for domestic tourists are the quality of attractions and for foreign tourists are quality of restaurants.